A New combination for the Philippine Apocynaceae - Sodusta, Patrick Jason A. (Phytotaxa, 2019)
Studies on the molecular systematics concluded the dissolution of the genus Sarcostemma Brown (1810: 463) (Meve & Liede-Schumann 2012), where it should be congeneric with Cynanchum Linnaeus (1753: 212). Consequently, several authors made new nomenclatorial combinations to transfer Sarcostemma to Cynanchum. However, in the Philippines, Sarcostemma malampayae Kloppenb., Cajano, & Hadsall (Kloppenburg 2015) is yet to be formally published of its new combination. Here I propose the new combination of the species under the genus Cynanchum.